Evaluation of effects of multipath and co-channel interference on time reversal multiple-input/multiple-output in underwater acoustic channel. (4th June 2018) - Kida, Yukihiro; Deguchi, Mitsuyasu; Shimura, Takuya
Abstract: The relationship between the performance of time-reversal-based multiple-input/multiple-output (MIMO) communication technique and the changes in the multipath environment is investigated quantitatively. In this study, the performance of adaptive time reversal (ATR)-MIMO is investigated by a parametric study approach. The ATR-MIMO communication technique is applied to the multipath-rich synthetic shallow sea acoustic dataset. We focused on discussing about the relationship among the changes in the multipath environment, the number of transmissions, the capability of ATR-MIMO to remove cochannel interference (CCI), and the efficiency of utilization of the energy of the multipath. The results reveal which characteristic of an acousticwavefield affects the performance of ATR-MIMO and how the performance saturates when the multipath environment changes. It is also demonstrated that ATR-MIMO can utilize the energy of the multipath as effectively as the passive-time-reversal-based single-input/multiple-output communication technique in a Gaussian-noise-dominant environment.